Representasi Gender pada Seni Lukis Kreativitas Anak - Muhammad Surya Gumilang (JURNAL RUPA, 2016)
Creative children paintings are not only meant as children's freedom of expressing their creativity in processing shapes and media. Moreover, the paintings can be creativity to read gender representation. Those paintings can read perfect gender representation. In addition children paintings can be seen by how representation of gender structures is in the object of children paintings, chosen color, idea that is expressed by the children. Therefore, seeing the creative children paintings will be seen how close the gender structures is in the paintings. This research used qualitative method with semiotic analysis approach. Result of the research shows that creative children paintings are read by three components of object meaning procedure, color, and idea, each phase of children growth can explain how gender is reflected in discourse representation.